PENGARUH PROGRAM MOTIVASI KEWIRAUSAHAAN DALAM MEMBENTUK JIWA KEWIRAUSAHAAN IBU RUMAH TANGGA - Raden Rudi Alhempi; Nia Anggraini; Mutia Ulfah (Jurnal Apresiasi Ekonomi, 2020)
This research was conducted in the city of Pekanbaru with the aim to determine the effect of entrepreneurial motivation to improve household welfare by empowering Housewives (IRT) as a productive workforce community. The majority of the residents of Limbungan Rumbai with the economic condition of middle-low class families, finding work is increasingly difficult, the need to meet daily needs is increasing. IRT in this region requires motivation in the form of knowledge and skills that can be used as provisions to start a business. The method of analyzing the data of this research is descriptive analysis, which is a research method that describes a situation and event on an actual problem and looks for facts with the correct interpretation as it is, and is not used as a broader conclusion maker. Based on the results of the study it was found that households need entrepreneurial motivation that can provide enlightenment of thought and understanding, especially to the IRT of the potential opportunities for family businesses so that growing interest and motivation in themselves to become entrepreneurs. IRT responds well to the large number of IRTs who ask questions related to problems starting a business and marketing. Keywords: Entrepreneur Motivation, Women's Empowerment, Womenpreneur